A sandwich structure assisted by defect engineering for higher thermoelectric performance in ZnO‐based films. Issue 3 (7th November 2020) - Zhou, Zhifang; Xu, Yushuai; Zou, Mingchu; Liu, Chan; Lan, Jinle; Lin, Yuan‐Hua; Nan, Cewen
Abstract: Gallium (Ga) doping together with low dimensionality has been a promising approach to improve thermoelectric performance of zinc oxide (ZnO) materials, due to the increase of carrier concentration and suppression of phonon transport. So far, the highest power factor of Ga‐doped ZnO (GZO) thin films has reached 280 μW m −1  K −2, which is still limited for practical applications. In this work, we have simultaneously optimized the electrical conductivity and Seebeck coefficient of GZO thin films using the combination of oxygen defects and sandwich structure (GZO‐ZnO‐GZO). Benefiting from energy filtering effect at the interface between GZO and ZnO layers and high oxygen vacancy concentration, the density of states (DOS) effective mass has been increased together with a relatively high carrier concentration. As a result, an improved power factor value of 434 μW m −1  K −2 at 623 K has been achieved, which is comparable to the best values reported for ZnO‐based films. This method of combining defect engineering and sandwich structure design shows great potential in enhancing the thermoelectric performance of ZnO‐based thin films or other oxide materials.